Crops that feed the world 7: Rice - Seck, P.A.; Diagne, A.; Mohanty, Samarendu; Wopereis, Marco C.S. (Springer, 2012)
Fears about global food security led to a spike in food prices in 2008, social unrest and pushed a further 100 million people into poverty. Prices remain high and volatile. In this paper we take a closer look at rice, a crop that feeds billions of people in the world, and focus in particular on Asia and Africa. On both continents, rice is grown in a wide range of climatic conditions, from river deltas to mountainous regions. Irrigated systems dominate in Asia and rainfed systems in Africa. Predicted demands for rice remain strong. An additional 116 million tons of rice will be needed by 2035 to feed growing populations. In Africa, where rice is the most rapidly growing food source, about 30 million tons more rice will be needed by 2035, representing an increase of 130% in rice consumption from 2010. About one-third of this extra rice will be needed in Nigeria alone. In Asia, per capita consumption of rice may go down in some mid- and high-income countries. Rice farming will need to produce about 8–10 million tons more paddy per year over the next decade. Without area expansion this will require an annual yield increase of about 1.2–1.5%, equivalent to an average yield increase of 0.6 t ha−1 world-wide. Improving global food security will, therefore, necessitate concerted efforts to increase the productivity of rice per unit of land, water and/or labor in Asia and Africa, and the development of new land and water resources in a responsible and equitable manner to counteract losses due to urbanization and industrialization. During 2007–2011, productivity increases in Africa have been leading the way, with paddy rice production levels increasing by 9.5% per year, compared to 1.6% in Asia. Priorities for rice sector development include (i) continued and increased research efforts to close yield gaps and raise yield ceilings across rice growing environments through varietal development and improved rice production methods, and coping with climate change in both continents and (ii) strengthened and equitable public-private sector partnerships and conducive policy environments in Africa, with special emphasis on mechanization of rice farming from land preparation to harvest and rice processing practices.